EC Anti-Corruption: Permainan Kartu Edukasi untuk Meningkatkan Pengetahuan Anak mengenai Pendidikan Antikorupsi - Nicholas Sebastian; Ida Ayu Kade Dian Indriyani; Luh Made Gita Prasanthi Dewi; I Made Sumerta Yasa; Isabel Evangeline; Ni Ketut Yuli Santosa (Jurnal Pendidikan Indonesia, 2024)
Abstract. Based on Indonesian Corruption Watch data, in 2017-2023 there were 3,681 corruption cases that brings on IDR 139.6 trillion losses for Indonesia state economy. Corruption can be prevented by anti-corruption education since childhood. Anti-corruption education has purpose to build children’s character aligned with anti-corruption values. Children like to play game with their peers, thus EC Anti-Corruption can be used for learning media to increase children’s knowledge of anti-corruption. The purpose of this research is to explore whether the EC Anti-Corruption can increase students’ knowledge of anti-corruption. This research has been held in 25th October until 17th November 2022. This research was conducted by doing literature study, pretest-posttest, questionairre, and experiment. The samples of this research were 36 fifth-grade students at SD Kristen Harapan Denpasar with convenience sampling technique. Based on the result of pretest and posttest, this media can increase 14.4% of sample’s knowledge of anti-corruption. Based on the Z test result, it was found P value < α, hence H0 was rejected and H1 was accepted. It is supported by 69,4% of the samples stated that their knowledge was increase after playing EC Anti-Corruption. In conclusion, EC Anti-Corruption can increase fifth-grade students’ knowledge of anti-corruption at SD Kristen Harapan Denpasar.